Reliable, resilient and sustainable water management: the Safe & SuRe approach. Issue 1 (17th June 2016) - Butler, David; Ward, Sarah; Sweetapple, Chris; Astaraie‐Imani, Maryam; Diao, Kegong; Farmani, Raziyeh; Fu, Guangtao
Abstract: Global threats such as climate change, population growth, and rapid urbanization pose a huge future challenge to water management, and, to ensure the ongoing reliability, resilience and sustainability of service provision, a paradigm shift is required. This paper presents an overarching framework that supports the development of strategies for reliable provision of services while explicitly addressing the need for greater resilience to emerging threats, leading to more sustainable solutions. The framework logically relates global threats, the water system (in its broadest sense), impacts on system performance, and social, economic, and environmental consequences. It identifies multiple opportunities for intervention, illustrating how mitigation, adaptation, coping, and learning each address different elements of the framework. This provides greater clarity to decision makers and will enable better informed choices to be made. The framework facilitates four types of analysis and evaluation to support the development of reliable, resilient, and sustainable solutions: "top‐down, " "bottom‐up, " "middle based, " and "circular" and provides a clear, visual representation of how/when each may be used. In particular, the potential benefits of a middle‐based analysis, which focuses on system failure modes and their impacts and enables the effects of unknown threats to be accounted for, are highlighted. The disparate themes of reliability, resilience and sustainability are also logically integrated and their relationships explored in terms of properties and performance. Although these latter two terms are often conflated in resilience and sustainability metrics, the argument is made in this work that the performance of a reliable, resilient, or sustainable system must be distinguished from the properties that enable this performance to be achieved. Abstract : Impact Statement Water management faces major challenges over the coming decades, with existing social, ecological, and technical water subsystems subject to emerging global threats such as climate change, urbanization, and depletion of resources. Current methods may be able to deal with these threats individually; however, recent experiences have revealed serious problems, and, without new ideas and approaches, levels of service will be challenged significantly by future change. This research, therefore, provides a framework that addresses the need to provide safe (reliable) water management that is also resilient and sustainable in the face of emerging threats and highlights opportunities for intervention. In doing so, it aims to provide greater clarity to decision makers, allowing better informed choices to be made. It also connects the additional global challenges of climate change, energy, food production, agriculture, and health, all of which may be threats to water management and/ or consequences of water system failure.